2013
DOI: 10.1159/000350558
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Sarcomatoid Change without Anticancer Therapies

Abstract: Hepatocellular carcinoma (HCC) with sarcomatoid change is a rare neoplasm of the liver, and recurrent therapies for HCC such as transcatheter arterial chemoembolization and percutaneous ablation therapy are presumed to promote sarcomatoid change. A 73-year-old man was admitted to our hospital diagnosed as having liver cancer originating from hepatitis C-related cirrhosis without any previous treatment for HCC. Ultrasonography showed that the tumor was hypoechoic, 3 cm in diameter, with unclear margins. Compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In another study that included 28 patients with sarcomatoid HCC, 19 patients (67.9%) had chronic hepatitis B and none had chronic hepatitis C. (23) The CT findings of sarcomatoid HCC have shown irregularly demarcated intrahepatic masses with delayed prolonged peripheral enhancement caused by rapid growth with central necrosis and hemorrhage as well as peripheral viable cancerous tissue. (24) In our study, the CT findings of approximately half of the patients showed hypodense or heterogeneous masses with a peripherally enhanced rim, central necrosis, and hemorrhage in the arterial phase. The tumor capsule was occasionally observed in some cases.…”
Section: Discussionsupporting
confidence: 49%
“…In another study that included 28 patients with sarcomatoid HCC, 19 patients (67.9%) had chronic hepatitis B and none had chronic hepatitis C. (23) The CT findings of sarcomatoid HCC have shown irregularly demarcated intrahepatic masses with delayed prolonged peripheral enhancement caused by rapid growth with central necrosis and hemorrhage as well as peripheral viable cancerous tissue. (24) In our study, the CT findings of approximately half of the patients showed hypodense or heterogeneous masses with a peripherally enhanced rim, central necrosis, and hemorrhage in the arterial phase. The tumor capsule was occasionally observed in some cases.…”
Section: Discussionsupporting
confidence: 49%
“…The true mechanism remains unknown. With the increase in reports of iCCA‐SC without previous anticancer therapy, sarcomatoid change has been increasingly considered to be due to the natural progression of cholangiocarcinoma, genetic expression alterations or stochastic phenotype switching . Seol et al determine the expression of genes related to cholangiocarcinoma sarcomatous transdifferentiation using DNA microarray technology.…”
Section: Discussionmentioning
confidence: 99%
“…Among 10 patients with ruptured HCC who underwent CEUS with Levovist and abdominal angiography, Matsumoto et al (9) found that CEUS was successfully used to differentiate active from inactive hemorrhage by detecting the contrast agent in ascites. In addition, Sugihara et al (10) found that CEUS with Sonazoid is effective for identifying bleeding sites on the hepatic surface after RFA based on the presence of jet-like high-intensity echoes in pleural effusion, although the findings could not be confirmed on color Doppler imaging.…”
Section: A B C Dmentioning
confidence: 99%